A FUZZY-BASED DECISION SUPPORT MODEL FOR EFFECTIVENESS EVALUATION – A CASE STUDY OF EXAMINATION OF BULLDOZERS - Tanasijevic, Milos; Jovancic, Predrag; Ivezic, Dejan; Bugaric, Ugljesa; Djuric, Radisa (International Journal of Industrial Engineering: Theory, Applications and Practice, 2020)
Effectiveness evaluation is one of basic components in engineering asset management. It is overall concept and represents measurement of quality of service level for selected engineering system. Effectiveness contains series of partial indicators related to time in operation and time for maintenance activities, as well as to functional properties of the system. This article describes analysis and structuring of partial indicators, as well as development of model for their synthesis to the level of effectiveness. Indicators have hybrid character (measured values and experts judgments), and the fuzzy inference model is suggested for their processing and integration into the effectiveness. This approach provided possibility for evaluation of a technical system in sense of decision making about remaining capabilities and optimization of life cycle costs. To demonstrate the opportunities of developed model for effectiveness evaluation, case study related to bulldozers is presented. Bulldozers are machines operating at difficult conditions, usually under pressure to achieve required performance with low stoppages and minimal costs during overall operational life. Case study included two approaches. First one is based on data collected by experts’ judgments, while the other one is based on measurement and statistical processing of data